Aggregation-Sex Pheromones and Likely Pheromones of 11 South American Cerambycid Beetles, and Partitioning of Pheromone Channels - Silva, Weliton D.; Zou, Yunfan; Bento, José M. S.; Hanks, Lawrence M.; Millar, Jocelyn G. (Frontiers in Ecology and Evolution, 2017)
Over the past decade, volatile sex and/or aggregation pheromones and pheromone candidates have been identified for well over 100 species in the large beetle family Cerambycidae, demonstrating that pheromone-based communication is crucial for effective mate location by these insects. Despite this rapid progress in elucidating the chemical ecology of Cerambycidae, most research to date has focused on species from North America, Europe, and Asia, with almost nothing known about species native to Africa, Australia, and South America. Here, we report the identification and field assessment of aggregation-sex pheromones produced by adult males of Ambonus distinctus (Newman) and Ambonus electus (Gahan), two sympatric and synchronic cerambycid species endemic to South America. Analyses of headspace volatiles from adult beetles showed that these species share two male-specific components, (R)-3-hydroxyhexan-2-one, and lesser amounts of 1-(1H-pyrrol-2-yl)-1,2-propanedione. Headspace volatiles from male A. distinctus also contained a novel minor component, identified as 3-methylthiopropan-1-ol. Field bioassays were conducted in Brazil, testing reconstructed blends of the compounds produced by each species, as well as racemic 3-hydroxyhexan-2-one and 1-(1H-pyrrol-2-yl)-1,2-propanedione as single components. Both sexes of A. distinctus and A. electus were most attracted to traps baited with their respective blends. In particular, 3-methylthiopropan-1-ol synergized attraction of A. distinctus and appeared to antagonize attraction of A. electus, suggesting a mechanism to minimize cross-attraction between these two congeners. Nine other cerambycid species were captured in significant numbers during the bioassays, including Ambonus interrogationis (Blanchard), Amorupi fulvoterminata (Berg), Chrysoprasis aurigena (Germar), Itaclytus olivaceus (Laporte & Gory), Neoclytus pusillus (Laporte & Gory), Orthostoma abdominale (Gyllenhal), Sphaerion inerme White, Stizocera consobrina Gounelle, and Uncieburia nigricans (Gounelle). Males of some of these species were found to produce (R)-3-hydroxyhexan-2-one, explaining why they had been attracted to some of the lures tested in bioassays. However, males of other species produced compounds other than 3-hydroxyhexan-2-one or 1-(1H-pyrrol-2-yl)-1,2-propanedione. We propose that these species are exploiting the pheromones of other guild members to locate high quality hosts for their larvae.